Detection of cracks in axially loaded tie-rods by vibration analysis. Issue 2 (2nd April 2020) - Collini, L.; Garziera, R.; Riabova, K.
ABSTRACT: Determination of the axial load acting on steel reinforcement tie-rods is of crucial importance for ensuring the effectiveness and safety of structures, especially in the case of ancient masonry buildings. Many non-destructive dynamic techniques have been proposed and successfully tested over recent decades; however, ancient tie-rods can be affected not only by excessive loads but also by cracks, flaws and localized damage due to ageing and environmental effects, resulting in hidden dangers. This work introduces an operative, simple technique for the detection of cracks in structural tie-rods based on analysis of the dynamic behaviour of the rod itself and estimation of the flexural compliance. The method, refined and validated with extensive laboratory tests, shows how the presence of a crack changes the natural frequencies, damping and compliance of the rod in a way that can be quantified and recognized in unknown situations. On the basis of these results, a novel quantitative damage index is defined for practical use.